STUDENT PERSONALITY TRAITS’ INFLUENCE ON PROFESSOR EVALUATION AND ON THEIR ACADEMIC ACHIEVEMENT IN KOSOVO - Duraku, Zamira Hyseni (European Scientific Journal, ESJ, 2014)
The purpose of this study was to describe and investigate the personality traits and characteristics influences on students’ evaluations about their professor assessment and on their academic achievement. One of the main theses of this analytical study was to determine whether there are differences on evaluating teachers and their assessments used among students with different personality traits. While the other main theses of this analytical study is to identify if there are differences among students with different personality characteristics and their achievement results. To identify the scope of this study, the quantitative research method has been used. The measuring instrument was designed in the form of a questionnaire that was conducted with the 1006 students who are currently pursuing their BA degree at University of Prishtina, Hasan Prishtina University, in Kosovo. For the conduction of the research, students were selected from the 12 departments within the university. Results of the study indicate that a great deal of the student body participating in the study did not believe in the fairness of their professor evaluations. Furthermore, there are differences between evaluations and students personality traits. According to the results, students who agreed that it is common for them to blame others and be reckless were also the least satisfied students with their professor evaluations.